The Impact of the PSP on Software Quality: Eliminating the Learning Effect Threat through a Controlled Experiment. (30th September 2014) - Grazioli, Fernanda; Vallespir, Diego; Pérez, Leticia; Moreno, Silvana
Abstract : Data from the Personal Software Process (PSP) courses indicate that the PSP improves the quality of the developed programs. However, since the programs (exercises of the course) are in the same application domain, the improvement could be due to programming repetition. In this research we try to eliminate this threat to validity in order to confirm that the quality improvement is due to the PSP. In a previous study we designed and performed a controlled experiment with software engineering undergraduate students at the Universidad de la República. The students performed the same exercises of the PSP course but without applying the PSP techniques. Here we present a replication of this experiment. The results indicate that the PSP and not programming repetition is the most plausible cause of the important software quality improvements.